Die deutschen Alpen - Prozeßabläufe spezieller Agrarstrukturen - Ruppert, Karl (ERDKUNDE, 1982)
The paper deals with the development of special agricultural structures in the German Alps. The differentiation between the agriculture in the Allgau region and in Upper Bavaria is emphasized, and the tendencies leading to the shifting of the main milk production areas to the edge of the Alps, and even to the pre-alpine regions, are demonstrated. The situation of the alps (alpine pastures) is dealt with, and it can be shown that this special form of pasture is still important and, contrary to frequent opinion, in no case decreasing. The problems connected with the separation of wood-land and pasture-land, a special form of high-alpine land consolidation, are discussed, and lastly a short report is given on the present situation of the pasture economy in the different alpine countries, together with remarks on measures taken in order to preserve the cultural landscape.